Reconciling the irreconcilable: Democracy and the National security exemption to the right to freedom of information - Martin, Patricia-Ann (Department of Public Law, 2021)
The prevailing South African Constitutional order is defined in the Constitution of the Republic of South Africa as a sovereign constitutional democracy. Freedom of access to government held information by the public is a fundamental and indispensable tenet of a sovereign constitutional democracy. The essential link between the two is recognized by the South African Constitution which guarantees the right to freedom of information as a fundamental human right. The Constitution simultaneously recognizes that all rights, including the right to freedom of information, may be subject to limitation. However, any such limitation must be reasonable and justifiable in an open and democratic society based on human dignity, equality, and freedom. The right to freedom of information is subject to often severe limitations in the arena of national security matters on the ground that the need for secrecy in this arena is self-evident. The limitation of the right may be necessary, but must, as in the case of all other limitations, be reasonable and justifiable in an open and democratic society. A comparative overview of most notably the United States of America, a stable and mature sovereign constitutional democracy, reveals that it, in the practical application of the limitation of the right to freedom of information in the arena of national security does not follow through on its commitment to democratic values. In the practical application of the limitation, the United States may be accused of failing to meet the standards required by a sovereign constitutional democracy in the extent of power it affords the unaccountable executive branch of government over the control and dissemination of information in the arena of national security. More specifically, in the power it affords this branch to define national security. And further, in its failure to hold this branch accountable for decisions made in this regard. This lack of accountability may be attributed to a conservative judiciary which as a matter of course defers to the executive and a failure on the part of the legislature to legislate alternative methods of accountability. The question for South Africa is whether it having Constitutionally entrenched the right to freedom of information, will be able, in contrast to the United States, to maintain democratic standards in the practical implementation of the limitation of the right to freedom of information in the arena of national security. Current practices in South Africa reveal that it has not been able to andwill not be able to maintain the necessary standards, without engaging in some fundamental changes. Primarily because of traditional arid entrenched judicial and public attitudes as well as because of the extensive power afforded the executive branch in respect of control of information in the arena of national security and over the definition of national security. The solution lies in a pro-active legislative programme designed to give effect to the right to freedom of information. Any such programme must actively limit the extent of discretionary power afforded the executive branch and where such power is necessary, make it subject to substantive review, in other words must enable one to hold the executive accountable for its decisions. One of the primary tools for achieving this is by way of freedom of information legislation. Such legislation must expressly, and in sufficient detail, regulate exemptions to the right in such a manner as to make the successful invocation of such an exemption dependant on whether it is reasonable and justifiable in an open and democratic society. Further, any allegation of reasonableness and justifiability must be open to public scrutiny in a manner which would not jeopardize legitimate secrets. The balancing of the competing interests poses a very real dilemma for any democratic society. This dilemma can however to a large extent be resolved by a change in judicial and public attitudes and legislative activism. Th,e process of change has commenced in South Africa. This is evidenced in the Constitutional terms and tone as well as in a number of legislative initiatives to change existing national security laws and to introduce new laws such as the current Open Democracy Bill.